Cidadania empresarial: o ardil da destituição do dissenso - Attila Magno e Silva Barbosa (Ciências Sociais Unisinos)
This article analyzes the results that corporate social responsibility projects have on the communities that benefit from them. The analysis is based on a case study on the company, ALBRAS SA, more specifically the two main projects it develops. Initially, it discusses the empowerment of transnational companies vis-à-vis the weakening of the national states at the present stage of capitalist development. At a second moment, it demonstrates that such projects are promoted by resorting to a discourse focused on the mobilization of the poor, in which the latter are considered for staying or not in a condition of poverty. Thirdly, it shows that such actions are inscribed in the instrumental rationality of the market, and for that reason they impose a set of management techniques as the only legitimate way of overcoming social deprivation and needs, which is an evidence of the anti-dissent character of this kind of action.